2018
DOI: 10.1111/ropr.12278
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Disruptive and Sustaining the Disrupted: The Case of Kodak and Fujifilm in the Face of Digital Disruption

Abstract: Valuable lessons can be learned from the comparison between Kodak and Fujifilm in terms of how the two companies confronted the digital disruption, with one failing and the other thriving. Through a series of theoretical propositions rooted in literature and tested with case studies on Kodak and Fujifilm, this article suggests a systematic way for incumbent firms to navigate technological disruptions. A disruptive technological change does not necessarily render all technological competences embedded in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 28 publications
0
8
0
3
Order By: Relevance
“…For å ta et berømt eksempel: I 1990-årene hadde Kodak et lukrativt globalt monopol på salg av kameraer og film. Fordi selskapet valgte å maksimere kortsiktig lønnsomhet og var treg med å investere i nye digitale teknologier, kollapset imidlertid lønnsomheten i løpet av et tiår til en brøkdel av sitt tidligere nivå (Ho & Chen, 2018). Dette var ikke på grunn av markedssvikt, men et tilfelle der markedet fungerte perfekt.…”
Section: Risiko Ved å «La Markedet Ta Seg Av» Norges Oljeunclassified
“…For å ta et berømt eksempel: I 1990-årene hadde Kodak et lukrativt globalt monopol på salg av kameraer og film. Fordi selskapet valgte å maksimere kortsiktig lønnsomhet og var treg med å investere i nye digitale teknologier, kollapset imidlertid lønnsomheten i løpet av et tiår til en brøkdel av sitt tidligere nivå (Ho & Chen, 2018). Dette var ikke på grunn av markedssvikt, men et tilfelle der markedet fungerte perfekt.…”
Section: Risiko Ved å «La Markedet Ta Seg Av» Norges Oljeunclassified
“…Ever-increasing competition together with increasing and changing customer demands place significant pressure on organisations to maintain and improve current products and services, as well as developing and renewing their offerings (Benner and Tushman, 2003;Ng et al, 2015). Organisations' success and survival have been shown to depend on this ability (Deming, 1993;Woodruff, 1997), since failure to fulfil customers' needs has been the downfall even of world-leading companies (Ho and Chen, 2018). Efforts to improve the quality of products and services from the customer's perspective is thus a central issue for organisations.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Kodama and Shibata (2016) proposed the concept of knowledge convergence through boundary vision from an in-depth case study of Fujifilm. Also, based on comparative case studies of Fujifilm and Kodak, Ho and Chen (2018) suggested there was a systematic way for incumbent firms to navigate technological disruption. They showed that disruptive technological change does not necessarily render all technological competences embedded in a firm's products obsolete.…”
Section: Introductionmentioning
confidence: 99%